Surface Electromyography for the Diagnosis of Tremor Syndrome: A Study of 97 Patients - Kartika Gulati; Sanjay Pandey (Annals of Indian Academy of Neurology)
Background and Objectives: Tremor is one of the most frequent movement disorders encountered in clinical practice with heterogeneous phenomenology and etiology. Surface electromyography (SEMG) is a noninvasive and reproducible test that can diagnose tremor syndromes. Methods: In this retrospective study, the clinical and electrophysiologic records of 97 consecutive patients with tremor syndromes who visited our movement disorder clinic between January 2023 and March 2024 were examined. Results: In our study, 28.8% (n = 28) of patients were of essential tremor (ET) syndrome. SEMG of ET syndrome patients showed synchronous bursts in 71.4% (n = 20), alternating bursts in 10.7% (n = 3), synchronous bursts with co-contraction of agonist and antagonist muscles in 10.7% (n = 3), and both synchronous and alternating bursts in 3.6% (n = 1) of patients. Tremor–ataxia syndrome formed 21.6% (n = 21) of our study population, with 71.4% (n = 15) of patients showing synchronous bursts and co-contraction and 28.6% (n = 6) patients having alternating bursts. Moreover, 12.3% (n = 12) patients were of parkinsonian tremor, of whom alternating bursts were present in 75% (n = 9) and synchronous bursts with co-contraction were present in 25% (n = 3) of patients. In addition, 11.3% (n = 11) of patients had dystonic tremor (DT), of whom 81.8% (n = 9) had synchronous bursts and co-contraction and 18.2% (n = 2) had alternating bursts. Conclusions: Synchronous bursts with co-contraction suggestive of DT were observed in most patients with tremor–ataxia syndrome and a small number of patients with ET syndrome. Our data suggests that SEMG helps differentiate these two clinical syndromes, which is difficult in a clinical setting.